Managing Suicidal Thoughts with DBT-Informed Social Work Counseling: Reflections on Working with a Filipino Young Adult - Meneses, Alain Matteo (Asean Social Work Journal, 2024)
Suicidal thoughts often serve as a precursor to suicide, which is a leading cause of death globally. In the Philippines, social work service users frequently present suicidal thoughts as an area of concern, yet the absence of standardized protocols and supportive systems complicates the role of Filipino social workers. Guided by Rolfe et al.’s Critical Reflection Model, this paper contemplates a social work helping process with a service user living with passive suicidal thoughts. Using a single case presentation, the paper illustrates the application of Dialectical Behavior Therapy (DBT)-informed social work counseling as an approach. Preliminary observations from the case suggest notable reductions in distress levels and underscore the importance of adapting and replicating the approach across diverse contexts. Additionally, the paper offers relevant practice insights drawn from the experience. It concludes with recommendations for advancing practice and future research in this critical area.